2001
DOI: 10.1254/jjp.85.358
|View full text |Cite
|
Sign up to set email alerts
|

Role of Reduced Glutathione and Nitric Oxide in the Black Tea Extract-Mediated Protection Against Ulcerogen-Induced Changes in Motility and Gastric Emptying in Rats

Abstract: ABSTRACT-The aim of the present study was to investigate the underlying mechanism of the role of hot water extract of black tea [Camellia sinensis (L). O. Kuntze Theaceae] in normalizing the changes in intestinal transit and gastric emptying induced by various ulcerogenic agents in experimental rats. Intestinal transit as well as gastric emptying were significantly reduced in rats treated with glutathione (GSH) depleting agents, diethyl maleate (DEM), indoacetamide (IDA) and N-ethyl maleimide (NEM). Prior oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Extensive work has been carried out regarding various medicinal attributes of green tea. The prophylactic action of the tea seed-derived triterpene saponins against ethanol-induced gastric mucosal lesions [49,50] and black tea extract against various ulcerogens [51,52] has been reported in rat models. Theaflavin (TF) is a major active component of black tea.…”
Section: Camellia Sinensismentioning
confidence: 99%
“…Extensive work has been carried out regarding various medicinal attributes of green tea. The prophylactic action of the tea seed-derived triterpene saponins against ethanol-induced gastric mucosal lesions [49,50] and black tea extract against various ulcerogens [51,52] has been reported in rat models. Theaflavin (TF) is a major active component of black tea.…”
Section: Camellia Sinensismentioning
confidence: 99%
“…Animal experiments have shown that a hot water extract of black tea (Camellia sinensis) promotes gastric emptying in rats, possibly as a result of inhibition of nitric oxide mediated relaxation of the stomach by thearubignins and theaflavins. 26 …”
Section: Limitations Of the Studymentioning
confidence: 99%
“…More recently, it has been reported that the increase in intestinal transit caused by BTE was reversed by l -NAME and l -NMMA and that restoration of intestinal nitric oxide synthase (NOS) activity was found to be associated with BTE treatment (Maity et al , 2001). It has also been reported that the l -arginine induced reduction of UGT was partially reversed by both BTE and l -NMMA and that both these agents (BTE and l -NMMA) caused a marked enhancement of the tonic 'hump' responses to transmural stimulation in guineapig ileum longitudinal muscle preparation (Chaudhuri et al , 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports from this laboratory indicate that while single administration of a 3% solution of BTE increased gastric transit (Chaudhuri et al ., 2000), chronic administration of a higher concentration of BTE, i.e. 10% solution failed to increase gastric transit (Maity et al , 2001). Apart from these studies and the antiulcer studies (Maity et al , 1995;1998) no other work has been carried out to investigate the effect of BTE on gastrointestinal function.…”
Section: Introductionmentioning
confidence: 98%